2017
DOI: 10.3389/fimmu.2017.01482
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 Present in Inflammatory Ascites from Advanced Epithelial Ovarian Cancer Patients Promotes Tumor Necrosis Factor Receptor 2-Expressing Regulatory T Cells

Abstract: BackgroundEpithelial ovarian cancer (EOC) remains a highly lethal gynecological malignancy. Ascites, an accumulation of peritoneal fluid present in one-third of patients at presentation, is linked to poor prognosis. High levels of regulatory T cells (Tregs) in ascites are correlated with tumor progression and reduced survival. Malignant ascites harbors high levels of Tregs expressing the tumor necrosis factor receptor 2 (TNFR2), as well as pro-inflammatory factors such as interleukin 6 (IL-6) and tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 95 publications
(104 reference statements)
6
60
0
1
Order By: Relevance
“…The data on effects of polyphenols on immune cells is increasing, especially in the context of cancer [130], with a lot of research understandably focusing on the effects on Tregs [131]. Modulating this cell type is especially important for ovarian cancer [132][133][134]. Curcumin can modulate Treg numbers and FoxP3 expression [135].…”
Section: Curcuminmentioning
confidence: 99%
“…The data on effects of polyphenols on immune cells is increasing, especially in the context of cancer [130], with a lot of research understandably focusing on the effects on Tregs [131]. Modulating this cell type is especially important for ovarian cancer [132][133][134]. Curcumin can modulate Treg numbers and FoxP3 expression [135].…”
Section: Curcuminmentioning
confidence: 99%
“…[62][63][64][65][66][67] Many cytokines and chemokines including TNF-α, IL-6, IL-8, and CXCL1 are significantly increased in serum, ascites or tumor samples of ovarian cancer patients. [7][8][9][10]30 Biological studies have shown that both ovarian tumor cells and tumor-infiltrating immune cells contribute to elevated levels of TNF-α and other inflammatory mediators in ovarian tumors. 1,2,6 As a primary pro-inflammatory factor, TNF-α acts as an endogenous promoter of a variety of oncogenic processes such as cellular transformation, survival, proliferation, invasion, angiogenesis, and metastasis.…”
Section: F I G U R Ementioning
confidence: 99%
“…1 TNF-α and other inflammatory mediators were detected at elevated levels in the serum and ascites of ovarian cancer patients. [7][8][9][10] It is now well established that, in addition to host immune cells, ovarian tumor cells are a clinically relevant source of these elevated inflammatory cytokines in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that molecules, such as IL-10, IL-4, and PGE2, are involved in the induction of differentiation into regulatory T-cells [22,26,30]. Since we identified increased levels of these mediators in co-cultures with MSCs, which are related to the inhibition of CD4 + and CD8 + T- Similarly, PGE 2 is a molecule that decreases T-cell proliferation, stimulates the secretion of IL-4 and IL-10 and promotes T-cell differentiation toward lymphocytes with the regulatory phenotype CD4 + CD25 + Foxp3 + [29].…”
Section: Mscs From Dental Tissues Induce a Similar Generation Of T-cementioning
confidence: 99%
“…Several studies have shown that molecules, such as IL-10, IL-4, and PGE 2 , are involved in the induction of differentiation into regulatory T-cells [22,26,30]. Since we identified increased levels of these mediators in co-cultures with MSCs, which are related to the inhibition of CD4 + and CD8 + T-cell proliferation and an increased frequency of CD4 + CTLA-4 + cells, we assessed whether these findings were related to the generation of regulatory CD4 + CD25 + CTLA-4 + and/or CD4 + CD25 + Foxp3 + T-cells (Figure 6a-c).…”
Section: Mscs From Dental Tissues Induce a Similar Generation Of T-cementioning
confidence: 99%